Solar energy monitoring system - Nurulhuda, Ngasiman (2009)
Solar energy is energy from the sun. This energy drives the climate and weather and supports virtually all life on Earth. Heat and light from sun, along with solar based resources such as wind and wave power, hydroelectricity and biomass, account for most the available flow of renewable energy. Solar power is becoming increasingly popular, as environment friendly renewable energy source that produces no pollution, requires minimal maintenance and energy from the sun is free. There many technologies for solar energy application through the residential, commercial, industrial, agricultural, and transportation sectors. The solar energy wide variety of technologies is flexibility. One types of Solar Energy system is Solar Photovoltaic Power. Photovoltaic Standalone system, Photovoltaic Hybrid system, Photovoltaic Grid Tie system is types of Solar Photovoltaic Power. Photovoltaic system use cell to convert sunlight into electricity. The PV cells consist of one or two layer of a semi conducting material, usually silicon. When light shines on the cell it creates an electric field across the layers causing electricity flow. So, the greater intensity of the light, the greater electricity flows. PV cells are referred to in terms of the amount of energy they generate in full sunlight; know as kilowatt peak or kWP. This project is to design a Solar Energy Monitoring System. The system use LCD to display as the meter to view that measurement of voltage and current in the system. The design uses a PIC micro controller (PIC 16F877) as control unit and optimizes the use of feature that exist in PIC micro controller such as analogue to digital converter (ADC). Then to design a signal conditioning circuit, which is, consist of transducers (voltage sensor and current sensor).